Impact of Corporate Name Change on Stock Prices: Evidence from BSE - Goyal, Priyanka; Goyal, Mansi (Gyan Management Journal, 2023)
The study examines the impact of the corporate name change on stock prices. By employing the event study methodology, efforts have been made to analyze how the market reacts to the corporate name change of companies during the years 2019 and 2020 listed on the Bombay Stock Exchange (BSE). The results suggested that corporate name change hardly impacts stock prices and shareholders’ wealth. Our findings also indicated that investors are rational in India. The t-test has been used to test the significance of the results. The study adds to the literature as few studies have been conducted in the Indian context that analyzed the impact of the corporate name change on stock market reactions and has provided inconclusive results.